Water and Energy Use Efficiencies of Sorghum Intercropped with Acacia Ililotica - Rao, A S; Ramakrishna, Y S; Singh, R S; Chopra, N K (Annals of Arid Zone, 2016)
The performance of sorghum grown as intercrop with 10 m widely spaced Acacia nilotica c.v. Cupercssifonnis tree rows was evaluated in an Indian arid region at Pali during 1988 to 1990. The grain yields of sorghum were 13-1.683 and 1-17 kg ha-1 and consumptive use values were 302.300 and 452 mm during 1988 to 1990. The water use efficiencies of the crop (w.r.t grain yield) were 0.-1-1.2.27 and 0.33 kg mm’! haÂ·1. whereas the energy use efficiencies (w.rl. biomass) of the crop were 0.-12. 0.17 and 0.16 per cent during these respective years. A. milotica trees during the three years of their growth did not interfere with intercrop for moisture and light.